Kinematic Analysis of the 2020 Elliot Creek Landslide, British Columbia, Using Remote Sensing Data - Donati, Davide; Stead, Doug; Geertsema, Marten; Bendle, Jacob M.; Menounos, Brian; Borgatti, Lisa (Frontiers in Earth Science, 2022)
The 2020 Elliot Creek landslide-tsunami-flood cascade originated from an 18.3 Mm3 rock slope failure in quartz diorite bedrock in a valley undergoing rapid glacial retreat. We used airborne LiDAR and optical imagery to characterize the slope and its surroundings. Using the LiDAR, we determined that two rockslides (2020 and an older undated one) occurred on this slope and shared a common basal rupture surface. We mapped two main sets of lineaments that represent structures that controlled the orientation of the lateral and rear release surfaces. Analysis of the topographic profile indicates a wedge-shaped failure block and a stepped rupture surface. Further topographic profile analysis indicates the possibility of a structurally controlled geomorphic step in the valley that corresponds with a change in the orientation of the valley. The rapid retreat of the West Grenville Glacier and the positions of the rupture surfaces suggest glacial retreat played a role in the landslides.